Evaluating the strategic implications of the service quality in green hotels from a new insight. Issue 13 (3rd July 2022) - Chang, Ya-Yuan; Cheng, Ching-Chan
ABSTRACT: This study aims to identify the strategic implications of the service attributes of green hotel from the implicit importance, Kano quality characteristics, and service risk. The results show that 12 service attributes are of high-importance, of which three are Attractive Quality, three are One-dimensional Quality, and six are Must-be Quality. Among three service attributes of Attractive Quality, two are low service risks. The findings can provide a reference for green hotels to improve service quality and avoid service failure. This study is an innovative approach in evaluating the service quality of green hotels.